Emerging Concept in DNA Methylation: Role of Transcription Factors in Shaping DNA Methylation Patterns. Issue 4 (April 2015) - Marchal, Claire; Miotto, Benoit
<x xml:space="preserve">Abstract</x> DNA methylation in mammals is a key epigenetic modification essential to normal genome regulation and development. DNA methylation patterns are established during early embryonic development, and subsequently maintained during cell divisions. Yet, discrete site‐specific de novo DNA methylation or DNA demethylation events play a fundamental role in a number of physiological and pathological contexts, leading to critical changes in the transcriptional status of genes such as differentiation, tumor suppressor or imprinted genes. How the DNA methylation machinery targets specific regions of the genome during early embryogenesis and in adult tissues remains poorly understood. Here, we report advances being made in the field with a particular emphasis on the implication of transcription factors in establishing and in editing DNA methylation profiles. J. Cell. Physiol. 230: 743–751, 2015. © 2014 The Authors. Journal of Cellular Physiology published by Wiley Periodicals, Inc.